2010
DOI: 10.1007/s00586-010-1328-7
|View full text |Cite
|
Sign up to set email alerts
|

Airway management in acute tetraplegics: a retrospective study

Abstract: The objective of this study was to develop an evidence-based airway management protocol for patients with acute tetraplegia. The method consisted of an analysis of the medical records of patients (September 1997-December 2002) with a spinal cord injury and a neurological deficit less than 8 weeks old. Of the 175 patients, 72 (41, 14%) were tracheotomised. This was influenced by the origin of the paralysis, Frankel score, and number of cervical spine operations, accompanying injuries and accompanying illnesses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A major risk factor affecting the need for tracheostomy was the number of spinal injury-specific comorbidities. The primary tracheotomy was performed according to the criteria proposed by Seidl et al, 7 which include neurological level C4-C8 lesions with ASIA scores of A or B, accompanying injuries or illnesses, and need for a combined surgical approach due to complex cervical spine trauma. 7 In addition, a tracheostomy was created when weaning took more than 4 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major risk factor affecting the need for tracheostomy was the number of spinal injury-specific comorbidities. The primary tracheotomy was performed according to the criteria proposed by Seidl et al, 7 which include neurological level C4-C8 lesions with ASIA scores of A or B, accompanying injuries or illnesses, and need for a combined surgical approach due to complex cervical spine trauma. 7 In addition, a tracheostomy was created when weaning took more than 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Before the first extubation attempt, patients had to meet the criteria presented in Table 2. Using the criteria of Seidl et al, 7 we performed tracheostomy when accompanying injuries, illnesses, complex cervical spine trauma, or a combined surgical approach required extended weaning for more than 4 days.…”
Section: Treatment Protocol and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The initial tracheotomy was carried out in accordance with criteria for patients with neurological level C4-8 after Seidl et al 21 The figures for tracheotomies performed (78%), patients with a tracheostomy (33%) and patients who were undergoing intermittent ventilation (11%) at the conclusion of the study were comparable with those from a retrospective study. 26 We did not observe the positive effect of abdominal FES on tracheostomy tube removal described by Lee et al 25 in a case study.…”
Section: Secondary Study Objectivesmentioning
confidence: 73%
“…20 Sample size was determined on the basis of historical studies which found that up to 70% of patients with paraplegia suffer from respiratory complications during the acute phase of their illness. 21 FES treatment should aim to reduce this to less than 50%. Assuming a (two-sided) level of significance of 5% and a power of 80%, the required sample size was estimated at 15.…”
Section: Study Endpointsmentioning
confidence: 99%